A critique of legal positivism in law enforcement against narcotics abusers in Indonesia - Salman Alfarisi; Kartina Eka Ningsih; Abdullah Khaliq (Privietlab, 2026)
Law enforcement against narcotics abusers in Indonesia is predominantly characterized by a punitive approach, resulting in prison overcrowding, despite the normative legal framework adopting a double-track system. This practice is deeply rooted in the rigid paradigm of legal positivism adhered to by law enforcement officials. This study aims to (1) analyze Hans Kelsen's legal positivism within the practice of narcotics law enforcement, and (2) critique the application of this positivism in achieving substantive justice. This research employs a normative (doctrinal) legal method, utilizing a case approach (Samarinda District Court Decision No. 1045/Pid.Sus/2019/PN Smr) and a statutory approach. The findings reveal two key points. First, the practice of law enforcement officials strictly reflects Hans Kelsen's Pure Theory of Law, focusing solely on das Sollen (fulfillment of statutory elements) while disregarding das Sein (the sociological fact that the suspect is an abuser). Second, the decision analysis exposes a paradox: while the judge's considerations were non-positivistic (acknowledging the need for rehabilitation), the final verdict remained positivistic (imposing imprisonment) due to the failure to conduct an integrated assessment at the investigation stage. It is concluded that rigid legal positivism fails to achieve substantive justice and utility, prioritizing only procedural legal certainty.